Diversity rules OK! the changing nature of families - Barrett, Barbara; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 2002)
Defines the different types of families and how their size and structure have changed over the years. Focuses on couple families, the blended or step family, sole parent families and the extended family. Other topics discussed include lesbian couple families, surrogacy, divorced families and the future of family life in an aging population
Title from title screen
Executive producer, Neil Barrett ; camera, Shannon Owen, Tim Mummery, Leigh Tilson ; editor, Conrad Trenton ; graphics, Reece Sanders, Robin Hely
Presenter: Andrea Waycott
Keywords: Family; Single parents; Divorce; Surrogate motherhood; Lesbian couples